Implikasi RUU App Bagi Kesetaraan Gender dan Perkembangan Seni - Effendi, Abd. Rahman (Musawa Jurnal Studi Gender dan Islam, 2006)
Problem of Pornography and pornoaksi progressively glow with the media appearance which lust. This problem then enter in public debate discourse, whether including art or porno. Then, this discourse enter in region of interefensi state, pass the invitor of RUU Anti Pornography and Pomoaksi (RUU APP). There is two citadel differ in answering to this RUU. Citadel supporting, what is supported by religion clan. and Citadel refusing, what is supported by actor faction. This article study the discourse in around RUU APP, in perpective religion clan, supporting, and actor faction, refusing. Solution also will explain the boundaries of term porno, its bearing with the artistic term and Gender term. Besides, this article will study how power relationship inviting of RUU APP with the restraint efforts to freedom of expression.